Harnessing Dendritic Cells for Tumor Antigen Presentation - Nierkens, Stefan (Molecular Diversity Preservation International (MDPI), 2011)
Dendritic cells (DC) are professional antigen presenting cells that are crucial for the induction of anti-tumor T cell responses. As a consequence, research has focused on the harnessing of DCs for therapeutic interventions. Although current strategies employing ex vivo-generated and tumor-antigen loaded DCs have been proven feasible, there are still many obstacles to overcome in order to improve clinical trial successes and offset the cost and complexity of customized cell therapy. This review focuses on one of these obstacles and a pivotal step for the priming of tumor-specific CD8(+) and CD4(+) T cells; the in vitro loading of DCs with tumor antigens.